UTILIZING A MODIFIED GFI METHOD TO IDENTIFY FLOOD PRONE AREAS DURING THE LA NINA PHENOMENON (CASE STUDY: EASTERN INDONESIA) - Haikal Fikri, Muhammad
La Nina is often associated with increased rainfall and flooding in Indonesia, particularly in the Eastern part of Indonesia. However, the relatively long La Nina period and the impact on a wide area, often makes it difficult to identify areas with the potential for flooding in detail. Mapping of flood threats using empirical methods, one of which is the Geomorphology Flood Index (GFI), has developed in the last decade giving hope that it can be implemented to identify flood-prone areas due to La Nina events. However, in general, empirical methods do not involve rain data in their calculations.